STUDENT INSIGHTS INTO WEB-BASED VERSUS TRADITIONAL LEARNING - BERDIKULOVA MUNIRA (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
The widespread integration of digital technologies in higher education has established web-based platforms as permanent alternatives to conventional classrooms. As academic institutions increasingly rely on diverse delivery formats, evaluating students’ experiences in these environments is essential for future curriculum development. Purpose: This study explores student insights into web-based versus traditional learning, aiming to evaluate and compare student engagement, academic comprehension, and overall educational satisfaction across both formats.